Functional deficiency in endogenous interleukin‐1 receptor antagonist in patients with febrile infection‐related epilepsy syndrome. Issue 4 (8th March 2019) - Clarkson, Benjamin D. S.; LaFrance‐Corey, Reghann G.; Kahoud, Robert J.; Farias‐Moeller, Raquel; Payne, Eric T.; Howe, Charles L.
Abstract : Objective: We recently reported successful treatment of a child with febrile infection‐related epilepsy syndrome (FIRES), a subtype of new onset refractory status epilepticus, with the recombinant interleukin‐1 (IL1) receptor antagonist (IL1RA) anakinra. On this basis, we tested whether endogenous IL1RA production or function is deficient in FIRES patients. Methods: Levels of IL1β and IL1RA were measured in serum and cerebrospinal fluid (CSF). The inhibitory activity of endogenous IL1RA was assessed using a cell‐based reporter assay. IL1RN gene variants were identified by sequencing. Expression levels for the secreted and intracellular isoforms of IL1RA were measured in patient and control cells by real‐time polymerase chain reaction. Results: Levels of endogenous IL1RA and IL1β were elevated in the serum and CSF of patients with FIRES (n = 7) relative to healthy controls (n = 10). Serum from FIRES patients drove IL1R signaling activity and potentiated IL1R signaling in response to exogenous IL1β in a cell‐based reporter assay. Functional assessment of endogenous IL1RA activity in 3 FIRES patients revealed attenuated inhibition of IL1R signaling. Sequencing of IL1RN in our index patient revealed multiple variants. This was accompanied by reduced expression of intracellular but not secreted isoforms of IL1RA in the patient's peripheral blood mononuclear cells. Interpretation: Our findings suggest that FIRES is associated with reduced expression of intracellular IL1RA isoforms and a functional deficiency in IL1RA inhibitory activity. These observations may provide insight into disease pathogenesis for FIRES and other inflammatory seizure disorders and may provide a valuable biomarker for therapeutic decision‐making. Ann Neurol 2019;85:526–537